Analysis of DVH Curves in Post-Mastectomy Breast Cancer Patients on PTV and Lung OAR Using IMRT Technique - Naura Shafila; Jerry Djohan; Saleha Saleha; Ajeng Anggreny Ibrahim; Ayu Harduanti Pratiwi; Sri Dewi Astuty; Syamsir Dewang (BULETIN FISIKA, 2025)
Breast cancer has become the most commonly suffered cancer in society, with approximately 66,271 cases of breast cancer in 2022. Breast cancer treatment can be carried out in various ways, one of which is radiotherapy, which has been proven effective in reducing recurrence rates and cancer symptoms. Treatment Planning System (TPS) is a device used for radiotherapy planning by optimizing the dose. One of the irradiation techniques that can be applied using TPS is the Intensity Modulated Radiation Therapy technique (IMRT). The research method uses the analysis of TPS planning results, namely DVH curve, which displays the dose distribution from the radiotherapy planning. The dose parameters analyzed are the Homogeneity Index (HI), Conformity Index (CI), and the dose comparison on the PTV and OAR according to QUANTEC, ICRU 62 of 1999, and ICRU 83 of 2010. The analysis was conducted statistically using SPSS and descriptively by examining the graphs formed from the calculations. The results obtained are HI values around 0,1–0,8, the CI value is 0,75–0,95, and the PTV95% value at 90% does not meet the ICRU requirement, which is PTV95% > 95%. The limits set by the ICRU are not met in all patients for PTV107%, which is PTV107% < 1%. The dose limits for the OAR lungs are met for all patients. However, in one patient, the dose received was very close to the QUANTEC limit, with the volume receiving a dose of 20 Gy being 29%, which is close to the QUANTEC limit of V20 < 30%.